Climate change and micro-organism genetic resources for food and agriculture: state of knowledge, risks and opportunities - Beed, Fenton D.; Benedetti, A.; Cardinali, G.; Chakraborty, S.; Dubois, T.; Garrett, K.A.; Halewood, Michael (Commission on Genetic Resources for Food and Agriculture, 2011)
This technical study focuses on the role of micro-organism genetic resources for agriculture and the influence of a changing climate. Agriculture is defined as crop-based food production for yield and quality. It excludes micro-organism genetic resources associated with livestock, fish and non-food-borne human pathogens. The study encompasses micro-organisms in five functional domains: soil inhabitants, plant and rhizosphere inhabitants, plant pathogens, biological control agents and food production systems. The scope of this study is vast as a consequence of the unrivalled diversity of micro-organism genetic resources for agriculture and the correspondingly huge variety of functions they perform, largely beneficial but also some harmful to agriculture. The study summarizes the role of micro-organism genetic resources for agriculture, provides examples demonstrating the potential influence of changes in climate on their performance, and describes their potential role in adapting agriculture to climate change and in mitigating changes in climate. While this study can only take preliminary steps towards detailing the complexity of the subject, the authors greatly appreciate the opportunity to increase awareness of micro- organism genetic resources for agriculture among the global community of decision-makers.